Pengaruh role stress, gender, struktur audit dan profesionalisme terhadap kinerja auditor bpk-ri perwakilan provinsi riau - Ramadika, Adhitio Pratama; Nasir, Azwir; Wiguna, Meilda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The study aimed to examine the role stress, gender, audit structure, andprofessionalism on auditor performance of BPK-RI representative Riau province.The sample was taken using the method of purposive sampling from BPKRIrepresentative Riau province. The sampling used was of 50 samples. Themethod of analysis in this study using multiple regression.The results of this study indicate that gender and audit structure effect onauditor performance. While role stress and professionalism does not effect on riskmanagement disclosure.Keyword: Role stress, gender, audit structure, professionalism, auditorperformance.